2020
DOI: 10.3390/electronics9030528
|View full text |Cite
|
Sign up to set email alerts
|

Is The Timed-Up and Go Test Feasible in Mobile Devices? A Systematic Review

Abstract: The number of older adults is increasing worldwide, and it is expected that by 2050 over 2 billion individuals will be more than 60 years old. Older adults are exposed to numerous pathological problems such as Parkinson’s disease, amyotrophic lateral sclerosis, post-stroke, and orthopedic disturbances. Several physiotherapy methods that involve measurement of movements, such as the Timed-Up and Go test, can be done to support efficient and effective evaluation of pathological symptoms and promotion of health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 73 publications
(114 reference statements)
0
20
0
1
Order By: Relevance
“…The inertial sensors embedded on mobile devices may help in the measurement of the results of the Heel-Rise Test. Previously, we proposed the creation of a personal digital life coach for the diagnostics of physical therapy [50]. The implementation of machine learning methods allows the creation of more accurate methods, and the development of these methods with technological equipment may increase the commodity and people's health.…”
Section: Discussionmentioning
confidence: 99%
“…The inertial sensors embedded on mobile devices may help in the measurement of the results of the Heel-Rise Test. Previously, we proposed the creation of a personal digital life coach for the diagnostics of physical therapy [50]. The implementation of machine learning methods allows the creation of more accurate methods, and the development of these methods with technological equipment may increase the commodity and people's health.…”
Section: Discussionmentioning
confidence: 99%
“…Such pre-processing can include basic validation of the user inputs by making sure that they are within reasonable ranges, or more advanced processing based on machine learning, signal processing, or time series analysis algorithms. For example, such methods can be implemented within a mobile application on the edge to identify patterns and measure the results of various functional tests, such as the Heel-Rise test [ 33 ], Sit-to-Stand test [ 34 ], Functional Reach Test [ 35 ], or the Timed Up and Go test [ 36 ]. In some cases, these tests’ results could be directly calculated within the mobile app and then provided as already-processed results to the cloud.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies [20][21][22] identified the different stages of the TUG test using the actual TUG test or similar settings, but we aimed to estimate the TUG test using normal ground walking with daily-life settings. Saporito et al introduced a remote mobility monitoring method by estimating TUG from free-living activities [23].…”
Section: Introductionmentioning
confidence: 99%
“…In many studies, various sensor locations were used for health and mobility assessment [5,[12][13][14][15][19][20][21][22][23][24]. Obviously, a wrist type of sensor is less obtrusive and more user convenient.…”
Section: Introductionmentioning
confidence: 99%